The Canopy App. - RODERICK, DAVID (Poetry, 2026)
The poem reflects on childhood memories spent in forested landscapes, evoking a sense of shelter and comfort reminiscent of fairy tales and maternal care. It contrasts the natural canopy of trees, once abundant but now nearly obsolete, with a modern digital app called Canopy that aims to recreate these immersive, soothing experiences through virtual screens of nature. The poem suggests that this app offers a way to reconnect with the calming textures and sensations of greenery, serving as a remedy for contemporary human grief linked to environmental loss.